Pengembangan Dan Pemasaran Padi Lokal Organik Pada Kelompok Tani Bangkit Serta Pemberdayaan Pemanfaatan Lahan Pekarangan Pada Kelompok Wanita Tani Putri Sejahtera - Friztina Anisa; Muhammad Habib Alfarizqi; Doni Agung Cahyono; Eliza Febriyani; Novia Dwi Rahmasari; Upik Milenia Jamin (Community Empowerment, 2022)
This integrated community service program (PPMT) was carried out in Mendak Hamlet, Banyuwangi Village, Bandongan District, Magelang Regency, Central Java in the form of developing and marketing organic local rice and utilizing yard land. The purpose of the program is to increase public awareness of organic local rice processing and make mothers aware of the use of home gardens to meet the healthy food needs. The implementation of this program is in the form of socialization, training for seeding vegetable seeds, practicing vegetable planting and catfish care, assistancing in making organic fertilizers and making cakes with local ingredients, and branding on organic rice (logos and packaging). The result of the training is that members of KWT Putri Sejahtera know how to seed and plant vegetables properly. Furthermore, through mentoring, farmer group members understand better how to make organic fertilizers and good cake processing. Another result of this program is that members of farmer groups become more aware of the importance of organic rice processing and have used the land in their home gardens to grow healthy vegetables.